Embedding gender in conservation agriculture R4D in Sub-Saharan Africa: Relevant research questions - Farnworth, Cathy Rozel; Badstue, Lone B. (International Maize and Wheat Improvement Center, 2017)
This resource examines the impact of gender relations on Conservation Agriculture (CA) adoption and adoption mechanisms. It offers a set of research questions to help integrate gender considerations into CA research for development, including on topics such as gender dynamics at the household and community level, minimum tillage, crop rotation and diversification, residue management, and knowledge networks.